PENGGUNAAN JAMBAN TRADISIONAL PADA MASYARAKAT TRANSISI DI SUMATERA SELATAN - Edi Harapan (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Healthy environment requires community participation, through clean water programs and providing healthy latrines for families as places to defecate. The use of traditional latrines is the main cause of pollution of river water and the surrounding air. In the case of river water is a basic requirement for the community. Changing the habit of people defecating in rivers has been carried out by the government through the provision of stimulants in the form of "squat toilets" in every household of poor families. Through this family latrine program, the people of South Sumatra are expected to have started to leave their habit of defecating in the river. This situation is very contradictory to the pattern of life of modern society, which has all led to the use of digital life, but in fact some rural communities in South Sumatra still live in traditional patterns.